2013
DOI: 10.1128/aem.02845-13
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Break Repair at −15°C

Abstract: The survival of microorganisms in ancient glacial ice and permafrost has been ascribed to their ability to persist in a dormant, metabolically inert state. An alternative possibility, supported by experimental data, is that microorganisms in frozen matrices are able to sustain a level of metabolic function that is sufficient for cellular repair and maintenance. To examine this experimentally, frozen populations of Psychrobacter arcticus 273-4 were exposed to ionizing radiation (IR) to simulate the damage incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…The metabolic activity of psychrotolerant and psychrophilic bacteria at subzero temperatures has been previously reported (e.g., Dieser et al, 2013;Junge et al, 2006;Mykytczuk et al, 2013); however, this is the first study that uses proteomics to elucidate some of the molecular mechanisms behind the ability of these bacteria to metabolize during extended periods of time at cold temperatures in saline ice. By combining metabolic assays (DNA and protein metabolism) with discoverybased proteomics, we provide direct evidence of metabolic pathways that allow C. psychrerythraea to survive at subzero temperatures.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The metabolic activity of psychrotolerant and psychrophilic bacteria at subzero temperatures has been previously reported (e.g., Dieser et al, 2013;Junge et al, 2006;Mykytczuk et al, 2013); however, this is the first study that uses proteomics to elucidate some of the molecular mechanisms behind the ability of these bacteria to metabolize during extended periods of time at cold temperatures in saline ice. By combining metabolic assays (DNA and protein metabolism) with discoverybased proteomics, we provide direct evidence of metabolic pathways that allow C. psychrerythraea to survive at subzero temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…Our leucine incorporation results showed protein synthesis in Cp34H down to −10°C over the course of 8 weeks. At very low temperatures, low rates of metabolism may offset cellular and macromolecular damage in permafrost bacteria (Dieser et al, 2013), thereby allowing for survival over prolonged time frames ). Maximum [3H]-leu incorporation occurred at the 24 h time point for all temperatures and was greatest in the −1°C treatment and lowest at −10°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a lot of studies testifies possibility of it. Microbial metabolism is revealed at temperatures at least down to −33 • C [88,89]. Moreover, it is shown that econiches with liquid water and positive temperatures can occur on the current Mars [88,[90][91][92][93].…”
Section: Implications For Habitability Assessmentmentioning
confidence: 98%
“…However, many microorganisms within the permafrost may not be completely dormant. For example, psychrophilic taxa isolated from the permafrost are capable of genome replication at temperatures as low as −20°C (Tuorto et al, 2014) and evidence of DNA repair has been found in taxa that have persisted in the permafrost for hundreds of thousands to millions of years (Dieser et al, 2013;Johnson et al, 2007). This does not suggest that there are no dormant microorganisms within the permafrost, as the generation-time effect can still occur if growth rate is correlated with season and the energetic cost of DNA repair is thought to be negligible (see section 2.2).…”
Section: Box 1 Dormancy In Low-energy Environmentsmentioning
confidence: 99%